(untitled) (Ameghiniana, 2014)
A new genus and species, Prostichomys bowni, from the early Santacrucian, Pinturas Formation, is described. This is the first record of Echimyidae for this formation. The molariforms are very similar to those of Santacrucian Stichomys, but they are more primitive in having upper molars more quadrangular in outline, less inclined crests, and labial flexii wider and more penetrating; the lowers have complete mesolophid in m1, absent in m3 and variably reduced in dp4 and m2; the lower incisors are posteriorly longer. Protacaremys (from the Colhuehuapian and Colloncuran ages) shows a dentition structurally ancestral to Prostichomys and is included in the Adelphomyinae herein. Protacaremys, Prostichomys, Stichomys and Adelphomys represent a single phyletic line different to the Prospaniomys-Spaniomys-Maruchito group (excluded from the Adelphomyinae hereín), Xilechimys-Paradelphomys group and Deseadomys. The intermediate evolutionary stage between the Colhuehuapian and Santacrucian genera of the dentition of Prostichomys is in agreement with the age inferred for the Pinturas Formation.